2002
DOI: 10.1073/pnas.162352299
|View full text |Cite
|
Sign up to set email alerts
|

Lytic replication-associated protein (RAP) encoded by Kaposi sarcoma-associated herpesvirus causes p21 CIP-1 -mediated G 1 cell cycle arrest through CCAAT/enhancer-binding protein-α

Abstract: Kaposi sarcoma-associated herpesvirus (KSHV) is an oncogenic DNA virus that causes Kaposi sarcoma and AIDS-related primary effusion lymphoma (PEL). Here we show that KSHV lytic cycle replication in PEL cells induces G1 cell cycle arrest, presumably to facilitate the progression of viral DNA replication. Expression of a KSHV-encoded early lytic protein referred to as RAP or K8 is induced within 12-24 h after the onset of lytic cycle induction in host PEL cells, and coincides with increased levels of both the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 30 publications
6
85
0
Order By: Relevance
“…It has been suggested that during the early stage of herpesvirus infection, cells are often blocked at G 1 stage to allow viral mRNA and proteins to be synthesized before the onset of cellular DNA replication. In previous studies, K-bZIP was shown to be a key cell cycle regulator that binds Cdk2 and activates p21 to slow down the cell cycle at the immediate-early stage of lytic infection (21,55). Accordingly, we suggest that, at the later stages of viral replication, vPK restores the Cdk2 function by phosphorylating Cdk2 targets, and vPK may compete with Cdk2, thereby releasing Cdk2 from its complex with K-bZIP.…”
Section: Discussionmentioning
confidence: 63%
“…It has been suggested that during the early stage of herpesvirus infection, cells are often blocked at G 1 stage to allow viral mRNA and proteins to be synthesized before the onset of cellular DNA replication. In previous studies, K-bZIP was shown to be a key cell cycle regulator that binds Cdk2 and activates p21 to slow down the cell cycle at the immediate-early stage of lytic infection (21,55). Accordingly, we suggest that, at the later stages of viral replication, vPK restores the Cdk2 function by phosphorylating Cdk2 targets, and vPK may compete with Cdk2, thereby releasing Cdk2 from its complex with K-bZIP.…”
Section: Discussionmentioning
confidence: 63%
“…Importantly, neither Zta nor K-bZIP are able to effect a cell cycle arrest in C/EBPa knock-out fibroblasts and cell lines (Wu et al, 2002. As detailed above, both Zta and K-bZIP physically interact with C/EBPa and stimulate the ability of C/EBPa to transactivate dependent promoters (Wu et al, 2002.…”
Section: Ability Of Zta and K-bzip To Regulate The Cell Cyclementioning
confidence: 96%
“…This appears to activate the transcriptional function of C/EBPa, leading to enhanced expression of C/EBPa and a downstream target, p21 CIP1 , which is thought to effect cell cycle arrest (Wu et al, 2002. The ability to activate C/EBPa and p21 requires the C-terminal half of both Zta and K-bZIP (Wu et al, 2002.…”
Section: C/ebpamentioning
confidence: 99%
See 1 more Smart Citation
“…C/EBPa expression is associated with increased expression of p21 cell cycle inhibitory protein (16), cell cycle arrest after viral infection (17), and terminal differentiation (18). Loss-of-function mutations in C/EBPa are pro-proliferative and have been reported in acute myeloblastic leukemia (19).…”
Section: Discussionmentioning
confidence: 99%